THE QUR'AN'S STATEMENT ABOUT THE ETIQUETTE OF DEALING WITH THE HOLY QUR'AN FROM SAYYID QUTB'S PERSPECTIVE IN HIS INTERPRETATION OF (ADH-DHILAL): AN ANALYTICAL STUDY: بَيَانُ القُرآنِ عَنْ آدابِ التّعَامُلِ تُجَاه القرآنِ مِنْ مَنْظُوْرِ سيد قُطُب فِي تَفْسِيْرِهِ (الظِّلَالِ): دِرَاسةٌ تحْلِيْليَّةٌ - Ridha, Ismu; Zinah, Manshur Mahmud Abu; Subhi, Muhibbul; Nasir, M. (Universitas Muhammadiyah Surakarta, 2024)
This study aims to address the hadith of the Qur'an about how to deal with the Holy Qur'an through the interpretation of “Shadows” by Sayyid Qutb. To achieve this, the researcher followed both (the inductive approach) by collecting Quranic verses that talk about how to deal with the Holy Qur'an, and then following the words of the author. (Shadows) on these (shadows) verses. This is followed by (the analytical approach) by analyzing those collected verses and finally (the deductive approach) by deducing the issues that appear in those studied verses related to the Qur'an's hadith about how to deal with it. The researcher reached several results, the first: paying attention to the Qur'an's explanation of how to deal with the Qur'an in order for the recitation of the Qur'an to be beneficial, to give its fruits through contemplation, and to be performed as the Messenger of God, may God bless him and grant him peace, performed it. The second: Among the etiquette of dealing with the Holy Qur'an is purity, which includes all types of purity, then listening and being attentive to it, then seeking refuge before reading it, and finally: recitation when reciting it, which is reading slowly and slowly, without haste.